2011
DOI: 10.3892/ol.2011.309
|View full text |Cite
|
Sign up to set email alerts
|

Three-gene signature predicts disease progression of non-muscle invasive bladder cancer

Abstract: Abstract.The clinical grades and staging methods currently employed for bladder cancer (BC) are inadequate for assessing treatment outcomes for non-muscle invasive bladder cancer (NMIBC). We have developed a clinically applicable quantitative real-time PCR (qPCR) gene signature to predict the progression of NMIBC. Three genes not previously described for BC were selected from our published progression-related gene classifier data set. Data were drawn from a previous study population and from new cases. Primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Considerable efforts have been made during the past years to identify expression-based prognostic biomarkers for bladder cancer at protein-coding genes and miRNAs levels [ 45 47 ]. More recently, accumulated evidence indicates that dysregulated lncRNAs are implicated in various tumorigenesis processes including proliferation, invasion and apoptosis by acting as tumor oncogenes or suppressor, which has developed a new area for biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable efforts have been made during the past years to identify expression-based prognostic biomarkers for bladder cancer at protein-coding genes and miRNAs levels [ 45 47 ]. More recently, accumulated evidence indicates that dysregulated lncRNAs are implicated in various tumorigenesis processes including proliferation, invasion and apoptosis by acting as tumor oncogenes or suppressor, which has developed a new area for biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous reports of genome-wide gene expression profiling of different bladder tumor groups highlighting the expression of clusters of genes indicative of specific tumor type [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], tumor behavior [ 22 , 23 , 24 , 25 ] or response to chemotherapeutic agents [ 26 , 27 ]. A similar approach has been taken with microRNA (miRNA) profiling where altered expression of specific miRNAs has been linked to bladder tumorigenesis [ 14 , 28 , 29 , 30 , 31 , 32 ] including predictors of outcome [ 33 , 34 , 35 , 36 ] and progression to muscle-invasive (MI) disease [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…CELSR receptor 3 (CELSR3) contains nine cadherin domains, which act as homophilic binding regions, and seven EGF-like domains involved in receptor-ligand interactions and cell adhesion, and is considered to serve a key role in cell-cell contacts ( 9 , 10 ). Dysregulation of CELSR3 DNA methylation is associated with several types of cancer, including pancreatic, hepatic, bladder and renal carcinomas ( 11 14 ). It has been reported that CELSR3 displays a cancer-specific pattern, and a 3.04-fold increase in its expression has been reported in tumor-associated stellate cells compared with inflammation-associated stellate cells ( 14 ).…”
Section: Introductionmentioning
confidence: 99%